Current state of the problem of habitual loss of pregnancy: discussion questions of causes and risk factors, tactics of periconceptive management - M Yu Skvortsova; S G Prilutskaia (IP Berlin A.V., 2017)
The literary review presents modern views on the problem of habitual loss of pregnancy. Questions of terminology, causes and risk factors, strategic directions of pre-survey examination and per-conceptual management of patients with this pathology are discussed. The causes of habitual loss of pregnancy are extremely diverse and, as a rule, are interrelated. These are genetic causes (chromosomal abnormalities of the embryo or one or both parents), endocrine disorders (the endpoint of which is a violation of the functional and structural state of the endometrium), immunological factors (realized at the level of local disruption of the production of various cytokines, normally providing implantation and placentation processes) and hemotaziologic disorders (the most studied of which is AFS). An important role of pre-gestational detection and correction of risk factors for pregnancy loss in a married couple is shown.